2002
DOI: 10.1017/s0252921100030505
|View full text |Cite
|
Sign up to set email alerts
|

AGNs in Shakhbazian Compact Groups

Abstract: The results of CCD spectroscopic observations of Shakhbazian compact groups of galaxies (SHCGs) with the 1.54-m (La Silla, Chile), 2.2-m (Calar Alto, Spain) and 2.6-m (Byurakan) telescopes are presented. According to these preliminary data, about 10% of member galaxies in SHCGs are emission-line galaxies (ELGs) including the broad-line AGNs (of classical Seyfert 1 type) and the narrow-emission-line galaxies.A research program has been developed in the University of Potsdam, Potsdam Astrophysikalisches Institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Hickson et al 1989aHickson et al , 1989bHickson et al , 1992Hickson 1993), Shakhbazian Compact galaxy Groups (ShCGs) have not been intensively investigated. The redshifts of only a few groups have been measured until recently (Robinson & Wampler 1973;Arp et al 1973;Mirzoyan et al 1975;Kirshner & Malamuth 1980;Amirkhanian 1987;Kodaira et al 1988Kodaira et al , 1990Kodaira & Sekiguchi 1991;Lynds et al 1990;del Olmo & Moles 1991;Tiersch et al 1995aTiersch et al , 1995bTiersch et al , 1995cTiersch et al , 1996aTiersch et al , 1999aTiersch et al , 1999b, the morphology of galaxies in a few groups was studied by Amirkhanian & Egikian (1987), Bettoni & Fasano (1995) and Tiersch et al (1995c).…”
Section: Introductionmentioning
confidence: 99%
“…Hickson et al 1989aHickson et al , 1989bHickson et al , 1992Hickson 1993), Shakhbazian Compact galaxy Groups (ShCGs) have not been intensively investigated. The redshifts of only a few groups have been measured until recently (Robinson & Wampler 1973;Arp et al 1973;Mirzoyan et al 1975;Kirshner & Malamuth 1980;Amirkhanian 1987;Kodaira et al 1988Kodaira et al , 1990Kodaira & Sekiguchi 1991;Lynds et al 1990;del Olmo & Moles 1991;Tiersch et al 1995aTiersch et al , 1995bTiersch et al , 1995cTiersch et al , 1996aTiersch et al , 1999aTiersch et al , 1999b, the morphology of galaxies in a few groups was studied by Amirkhanian & Egikian (1987), Bettoni & Fasano (1995) and Tiersch et al (1995c).…”
Section: Introductionmentioning
confidence: 99%
“…After removing galaxies whose velocities differ from the group median by more that 1000 km s −1 , Hickson et al (1992) found that t d ∼ 0.02H −1 0 and obtained a mean mass-to-light ratio of 50h (solar units) for the HCGs. Similar values were found for several Shakhbazian groups (Tikhonov 1986, Amirkhanian & Egikian 1987, Amirkhanian 1989, Lynds et al 1990, Amirkhanian et al 1991. Since the mass-to-light ratios of individual HCG galaxies is on the order of 7h (Rubin et al 1991), the galaxies appear to contain only ∼ 15% of the total mass.…”
Section: Dynamical Propertiessupporting
confidence: 77%
“…Radial velocities were determined for objects # 1, 2, 3, 5 and 8 by Amirkhanian & Egikian (1987) and for objects #1 to #8 by Tiersch et al (2002, hereafter T02); the median radial velocity is 11 890 km s −1 . All galaxies in this group are E and S0 types.…”
Section: Shcg 166mentioning
confidence: 99%